FAKTOR PENENTU PENGUNGKAPAN INTELLECTUAL CAPITAL (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Wahyu Aprilia, 13.05.52.0206; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2017)
This study examines and analyzes the influence of company size, leverage, profitability, age and independent commissioner to intellectual capital disclosure. Company size, leverage, profitability,age and independent commissioner which is the independent variable in this study. Disclosure of intellectual capital is the dependent variable. The total sample was 90 banking companies listed at BEI start from 2013 to 2015 were determined through purposive sampling. This study analyzed the annual reports of companies using content analysis. Data analysis was performed with the classical assumption, hypothesis testing and regression analysis method. The results showed that the size of the company, profitability, and independent commissioner positive effect, while the leverage and age of the company has no effect on intellectual capital disclosure.Keywords:Â Size, Leverage, Profitability, Company Age, and Independent Commissioner, Intellectual Capital Dislosure